Reality of Green Human Resource Practices GHRM: An Exploratory Study of the Opinions of a Sample of Employees at Jazan University - Rayani, Amal Mohammed Hadi (The Arab Journal of Administration, 2025)
The study aimed to identify the reality of the application of green human resource management practices (green employment, green training and development, green performance evaluation, green rewards) at Jazan University, and to identify the extent of the university’s tendency towards using environmentally friendly practices, as well as identifying the obstacles facing the university administration in green management application. To achieve the objectives of this study, the researcher relied on the descriptive analytical method. The sample of the study at Jazan University reached (301) out of (1379) administrative staff, where they were selected in a non-probability coincidence sampling method, and the questionnaire was relied on as a main tool for data collection and analysis. Among the most important findings of the study are: that the reality of green human resource management practices (green employment, green training and development, green performance evaluation, green rewards) at Jazan University came with a (high) degree of practice in general, and that the study members agreed on the obstacles that the university administration faces in the application of green management, where the overall average of the axis (3.82 out of 5.0), and based on this, the researcher made recommendations, the most prominent of which were: The university administration must adopt strategic plans to preserve the environment and include environmental goals in the university’s mission and vision, and it is necessary to provide Appropriate material and moral incentives related to preserving the environment, and attention must be paid to holding training courses and seminars and practicing them in a practical manner. Finally, several proposals were presented for future studies.